Langerhans Cells Directly Interact with Resident T Cells in the Human Epidermis - Tomonori Oka; Tatsuya Hasegawa; Truelian Lee; Valeria S. Oliver-Garcia; Mahsa Mortaja; Marjan Azin; Satoshi Horiba; Sabrina S. Smith; Sara Khattab; Kathryn E. Trerice; Steven T. Chen; Yevgeniy R. Semenov; et al. (JID Innovations)
Adult human skin contains nearly twice as many T cells as the peripheral blood, which include tissue-resident memory T cells. However, the precise mechanisms maintaining tissue-resident memory T cells in the healthy skin remain unclear. Using normal human skin samples, we find that Langerhans cells (LCs) contact T cells in the epidermis of the elderly. LCs with high HLA-II, CD86, and PD-L2 expression directly contacted PD-1+ tissue-resident memory T cells and CTLA-4+ regulatory T cells in the epidermis, indicating an axis of peripheral tolerance in a steady state. Environmental insults, UVB radiation, and hapten downregulated HLA-II and CD86 on LCs in the epidermis, suggesting that disruption of LC–T cell tolerogenic axis contributes to skin inflammation. Interestingly, immune checkpoint blockade therapy was associated with decreased epidermal LC–T cell contact in the normal skin of patients with cancer affected by cutaneous immune-related adverse events. Collectively, our findings indicate that LCs may contribute to T cell tolerance in the epidermis.